Barus sebagai Titik Nol Islam Nusantara: Tinjauan Sejarah dan Perkembangan Dakwah - Uky Firmansyah Rahman Hakim (Institut Agama Islam Negeri Bengkulu, 2019)
The decision to establish Barus City in Center of Tapanuli as the zero point of Islam Nusantra caused a mixed reaction from the Indonesian Historian. During this time the public knows that Islam first entered Indonesian territory in Aceh. But long before that the teachings of Islam already existed in Barus. This paper will provide an overview of the traces of the entry of Islamic teachings and evidence of the establishment of the Islamic Archipelago and the development of da'wah in Barus. Islam before being preached to Barus about the fifth century BC in Barus as evidence is the site of Mahligai, Papan Tinggi, Makham Tuan Makhdum whose gravestone reads kaligarafi verses of the Koran. Sheikh Mahmud played a major role in providing Islamic teachings through trade in the city of Barus. At present the lack of preachers makes the glory of Islam in the City of Barus decline, recitation is also rarely done and adolescent association is also mixed. This study further explains the impact of the development of Barus in the present.